Pengaruh Konsentrasi Crude Enzim Bacillus subtilis terhadap Kadar Gula dan Bioetanol Hasil Fermentasi Kulit Singkong Menggunakan Zymomonas mobilis - Nurusman, Arief Abdillah; Widyaningrum, Trianik; Nisa, Rifda Khairun; Utami, Listiatie Budi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Bioethanol is an environmentally friendly and renewable alternative fuel. The use of alternative fuels is necessary because petroleum fuels make a major contribution to increasing greenhouse gas concentrations, especially CO2. Bioethanol can be obtained from materials containing carbohydrates such as cassava peel which has a high carbohydrate content, namely 4.55%. The aim of this research was to see the effect of the crude enzyme concentration of Bacillus subtilis on the results of sugar and bioethanol content of cassava peel fermentation with Zymomonas mobilis and to find out the crude enzyme concentration that had the greatest influence. This research is an experimental study with the independent variable, namely the concentration of crude cellulase enzyme B. subtilis with concentrations of 0%, 2.5%, 5%, 7.5%, 10%, 12.5%, 15%, and 17.5% , and the dependent variables are sugar content from hydrolysis and bioethanol content from the fermentation process. The data obtained were analyzed using the ANOVA test and Duncan's test. The results of research on the effect of crude Bacillus subtilis cellulase enzyme concentrations of 8 concentrations have an influence on the amount of sugar and bioethanol produced from fermentation of cassava peel with Zymomonas mobilis. Crude Bacillus subtilis cellulase enzyme with a concentration of 17.5% had the greatest influence on sugar and bioethanol levels with a sugar content of 0.37% and a bioethanol content of 1.67%.